2017
DOI: 10.3892/ol.2017.5604
|View full text |Cite
|
Sign up to set email alerts
|

TRIM24 promotes the aggression of gastric cancer via the Wnt/β-catenin signaling pathway

Abstract: Abstract. Tripartite motif-containing 24 (TRIM24) is important in tumor development and progression. However, the role of TRIM24 in gastric cancer (GC) and the mechanisms underlying the dysregulated expression of TRIM24 remain to be fully elucidated. In the present study, it was found that TRIM24 was frequently overexpressed in GC cell lines and tissues compared with normal controls, as determined by western blotting and immunohistochemical staining. The high nuclear expression of TRIM24 was correlated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“…As for TRIM24, it is a member of the tripartite motif (TRIM) family [20], and the oncogenic role of TRIM24 in carcinogenesis has been demonstrated in several cancer types [43][44][45]. Moreover, our study identified that inhibited miR-138-2-3p or promoted TRIM24 stimulated Wnt/β-catenin activation in glioma cells, which was in line with the previous studies [21,41]. Wnt/β-catenin controls diverse cellular processes and drives cancer progression [46], with its activation revealed to promotes tumorigenesis of multiple cancers [47,48], including glioma [23].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As for TRIM24, it is a member of the tripartite motif (TRIM) family [20], and the oncogenic role of TRIM24 in carcinogenesis has been demonstrated in several cancer types [43][44][45]. Moreover, our study identified that inhibited miR-138-2-3p or promoted TRIM24 stimulated Wnt/β-catenin activation in glioma cells, which was in line with the previous studies [21,41]. Wnt/β-catenin controls diverse cellular processes and drives cancer progression [46], with its activation revealed to promotes tumorigenesis of multiple cancers [47,48], including glioma [23].…”
Section: Discussionsupporting
confidence: 90%
“…TRIM24 is a member of the TRIM family with its oncogenic role being identified in prostate cancer [20]. In addition, TRIM24 has been suggested to promote cancer progression by triggering the Wnt/β-catenin signaling pathway [21,22]. This pathway has been noted to be closely associated with cellular proliferation, migration, and angiogenesis and the following glioma malignancy [23].…”
Section: Introductionmentioning
confidence: 99%
“…For example, certain studies have identified that TRIM24 is overexpressed, and promotes cancer cell growth and invasion in bladder cancer and cervical cancer, possibly via the nuclear factor-κB and PI3K/Akt signaling pathways (36,37). Similarly, it has been reported that TRIM24 can accelerate cell growth and facilitate gastric cancer progression by activation of the Akt pathway (37) and the Wnt/β-catenin signaling pathway (38). Notably, in contrast to the aforementioned studies that suggest TRIM24 is an important oncogene in tumor development, TRIM24 has been identified to suppress the progression of murine hepatocellular carcinoma (39).…”
Section: Discussionmentioning
confidence: 97%
“…Immunohistochemistry was performed as previously described. 21 Briefly, slides went through antibody incubation overnight at 4°C with TRIM44 antibody (11511-1-AP; Proteintech, Chicago, IL, USA). The staining scores were then evaluated by two independent pathologists.…”
Section: Methodsmentioning
confidence: 99%